To find the numerical equivalent of 9^9 x 9^-6, we can simplify the expression.
9^9 = 387,420,489 (9 raised to the power of 9)
9^-6 = 1/9^6 = 1/531,441 (9 raised to the power of -6)
Therefore,
9^9 x 9^-6 = 387,420,489 x (1/531,441)
Simplifying further, we can divide 387,420,489 by 531,441:
387,420,489 / 531,441 = 729
So, the numerical equivalent of 9^9 x 9^-6 is 729.
find the numerical equivalent of 9^9 x 9^-6
3 answers
are you sure?
Apologies for the mistake. Let's recalculate correctly.
9^9 = 387,420,489 (9 raised to the power of 9)
9^-6 = 1/9^6 = 1/531,441 (9 raised to the power of -6)
Therefore,
9^9 x 9^-6 = 387,420,489 x (1/531,441)
Multiplying the two fractions:
(387,420,489 x 1) / 531,441 = 387,420,489 / 531,441
Simplifying the fraction:
387,420,489 / 531,441 = 729
So, the correct numerical equivalent of 9^9 x 9^-6 is indeed 729.
9^9 = 387,420,489 (9 raised to the power of 9)
9^-6 = 1/9^6 = 1/531,441 (9 raised to the power of -6)
Therefore,
9^9 x 9^-6 = 387,420,489 x (1/531,441)
Multiplying the two fractions:
(387,420,489 x 1) / 531,441 = 387,420,489 / 531,441
Simplifying the fraction:
387,420,489 / 531,441 = 729
So, the correct numerical equivalent of 9^9 x 9^-6 is indeed 729.